Noken politics and political Noken: symbol of communication in Papuan community - Warami, Hugo; Mofu, Suriel Samuel (Penerbit Universiti Kebangsaan Malaysia, 2024)
This article aims at revealing the Noken Politics and the Political Noken as a symbol of communication in the Papuan community. Philosophically, Papuan noken contains noble human values of Papuan civilization amid a globalized flow of communication and information in the life of the nation and state. In this article, Papuan Noken, which is an intangible cultural heritage, is explored based on antropolinguistic and communication perspectives. The focal point of this study consists of two parts, namely: (1) Noken Politics; and (2) Political Noken. As interdisciplinary research, this study applies two approaches, namely (1) theoretical approach and (2) methodological approach. The theoretical approach consists of symbolic interactionism theory and anthropolinguisti theory, while the methodological approach consists of a descriptive approach with an explanative dimension. In the perspective of symbolic and anthropolinguistic interactionalism, this study applies scientific principles to language data and adapts the steps of scientific studies in other fields of science. This study is conducted through the following procedures (1) providing data, (2) analyzing data, and (3) presenting the results of data analysis. The findings of this study reveal that Noken politics is one of the national policies for Papua which contains special planning, direction, and provisions (affirmations) that can be used as a basis for the overall processing of the system of government, politics, socio-culture in Papua. Noken politics is a policy that includes: (1) Noken Election System, (2) Clothing System, and (3) Noken Cultural Education System. Political noken is a term used to refer to noken cultural practices that contain political meaning. The meanings contained in the political noken are (1) the meaning of power, (2) institutional meaning, and (3)the meaning of conflict.